Effects of pH, temperature and hydraulic disturbance on nitrogen release from sediments in the Sunxi River, Three Gorges Reservoir Area, China - Yihong Ning; Bin Gao; Haiyan Wang; Wenning Hou (PeerJ)
To clarify the influence of changes in the overlying water environment on internal nitrogen release from reservoir sediments, we collected surface sediments at a depth of approximately 10 cm from the Sunxi River in the tail area of the Three Gorges Reservoir area for simulation experiments. By using orthogonal simulation experiments in the laboratory, we studied the effects of water pH, temperature and hydraulic disturbance on nitrogen release in the sediment and established a quantitative linear relationship between the nitrogen release rate from the sediment and the environmental factors of the overlying water. The results indicated that the average concentrations of total nitrogen (TN) and total phosphorus (TP) in the sediment were 430 mg/kg and 200 mg/kg, respectively. The sediment TN concentration had a very significant positive correlation with the sediment organic matter content (P < 0.001). The sediment TN, NO3-N and NH4-N release intensities gradually increased with increasing incubation time, with maximum release rates of 29.24 mg/((m2⋅d), 23.11 mg/(m2⋅d) and 4.32 mg/((m2⋅d), respectively. Range analysis revealed that the significance of the effects of environmental factors on sediment TN and NH4-N release were ranked as follows: temperature > pH > disturbance, and that of NO3-N release was ranked as pH > temperature > disturbance. Temperature plays the most important role in the behavior of different forms of nitrogen release from sediments. The capacity and potential for nitrogen release from sediments offer crucial insights for assessing the risks posed to the overlying water and highlighting the importance of these factors in water quality management and prediction in the reservoir area.